Ethnicity and Gender Comparisons of Health Consequences in Adults with Alcohol Dependence - Chartier, Karen G. (2013)
The moderating effects of ethnicity and gender on factors associated with physical health consequences in adults with alcohol dependence was examined using data from the 2001–2002 U.S. National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). Black and White respondents with a lifetime diagnosis of DSM-IV alcohol dependence were selected for the study (n = 3,852). A multiple-group structural equation model tested ethnicity, gender, and intervening variables as predictors of physical health status in alcohol dependent men and women. Study findings offer implications for clinical practice with alcohol dependent individuals by identifying likely target groups and problems for intervention.